Analisis Potensi Danau Ranamese sebagai Daya Tarik Birdwatching di Kabupaten Manggarai Timur - I Putu Andre Adi Putra Pratama; I Gede Gian Saputra; Putu Ade Wijana; I Gusti Ngurah Oka Widjaya (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Ranamese Lake in East Manggarai Regency has a high potential as a birdwatching destination due to its rich endemic avifauna and scenic natural landscape. However, this potential has not been optimally managed, particularly in terms of interpretation, facilities, and institutional management. This study aims to analyze the potential of Ranamese Lake as a special interest tourism destination using the 4A approach (Attraction, Accessibility, Amenities, Ancillary). The research employed a combination of primary and secondary data, including non-participatory field observations, in-depth interviews with managers, local government, and community members, as well as documentation from the Natural Resources Conservation Agency (BKSDA). The results indicate that the site’s attraction is very high, with the presence of endemic bird species such as Otus alfredi, Corvus florensis, and Pachycephala nudigula, although interpretation and tourism packaging remain suboptimal. Accessibility is relatively good, but trekking paths require improvements to ensure visitor safety and comfort. Existing facilities (amenities) are limited to basic and recreational infrastructure, making the development of low-impact bird hides, interpretive boards, and educational trails essential. Regarding institutional support (ancillary), strengthening the capacity of specialist guides and establishing clear collaboration between BKSDA, local government, and the community are key to sustainable destination management. Overall, Ranamese Lake has significant potential to be developed into a conservation-based special interest tourism destination by integrating ecosystem preservation, education, and high-quality visitor experiences.